Behavioral and social determinants of early childhood caries among Palestinian preschoolers in Jerusalem area: a cross-sectional study - Elham Kateeb; Sungwoo Lim; Saif Amer; Amid Ismail (BMC, 2023)
Abstract Background This study came to determine the prevalence of Early Childhood Carries (ECC) among preschoolers in a marginalized population and describe the influence of behavioral and social determinants on the development of ECC. Methods This is a cross-sectional study that was carried out in four random preschools in the Jerusalem Governorate of the Occupied Palestinian Territories. All children aged 3-5 years old in the selected schools were screened for ECC using the decayed, missing, and filled teeth index (dmft). Data on children's socio-economic, feeding habits, hygiene habits, access to care, parental level of stress, social support, and locus of control were collected by a validated questionnaire sent to the children's main caregivers. Descriptive statistics were generated and bivariable and multivariable analyses were used to explain the influence of different behavioral and social determinants on ECC levels. Results Four hundred and fifty-seven preschoolers completed the questionnaire and the clinical screening. Ninety-seven percent (n = 447) had experienced dental decay, with an average dmft score of 6.6 ± 4.3. After accounting for potential confounding, parents' internal locus of control was associated with lower dental caries among children (IRR = 0.97, 95% CI = 0.97, 0.98). Having routine, preventive visits versus never seeing a dentist were associated with lower dmft scores (IRR = 0.42, 95% CI = 0.33, 0.52). Night feeding habits (putting things other than water in the baby bottle at night, having children sleep while being breastfed at night) were positively associated with children's dental caries (IRR = 1.06, 95% CI = 1.04, 1.09: IRR = 1.15, 95% CI = 1.03, 1.29, respectively). Not adding sugar to the bottle was negatively associated with children's dental caries (IRR = 0.86, 95% CI = 0.74, 1.00). Conclusions Preschoolers in this study suffered from high dental caries experience. Although infant feeding habits were key factors in explaining the elevated level of the disease, system and socio-psychological factors were also detrimental to ECC prevalence. Policies and interventions to alleviate the burden of ECC need to address socioeconomic determinants of health in addition to feeding and hygiene practices.